Professor Zagorovsky’s(the second half of XIX c.) elaboration of issues of contractual rights in Kyiv Rus - Hrechenko, Volodymyr; Martseliak, Oleh (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article refers to the masterpiece by the legist professor’s Zagurovsky’s O.I. who worked at Kyiv, Kharkiv and Odessa (Novorossian) Universities and made a great contribution to the research of the law in Kyiv Rus. A lot of attention is drawn to his scientific views on contractual right in Old Russian society, especially its subjects, kinds of contracts and reasons of origin.